Prognostic value of duration of illness and early intervention in bulimia nervosa: a systematic review of the outcome literature - Reas, Deborah Lynn; Schoemaker, Casper; Zipfel, Stephan; Williamson, Donald A. (The international journal of eating disorders, 2001)
Early intervention is often regarded as an important step for the prevetion of a chronic eating disorder. The primary aim of this review was to systematically evaluate the outcome literature and to better describe the effects of early intervention on the course of bulimia nervosa.